A bibliometric analysis of the Jamasan Pusaka tradition in cultural documentation - Azzahra, Azizah; Khadijah, Ute Lies Siti; Rodiah, Saleha (Faculty of Communication, Padjadjaran University, 2025)
Background: Jamasan Pusaka is a traditional Indonesian ritual involving the ceremonial cleansing of sacred heirlooms such as keris, spears, and gamelan to preserve spiritual and historical heritage. In the era of globalization, this practice faces challenges in maintaining its relevance and authenticity, underscoring the importance of systematic documentation and scholarly attention. Purpose: This study aims to comprehensively the intellectual landscape of Jamasan Pusaka studies by identifying key trends, collaboration patterns, and dominant themes, while also examining imbalances in scholarly voices and perspectives within the discourse.Methods: A bibliometric analysis was conducted using data from the Scopus database spanning 2010 to 2025. The analysis examined publication outputs, citation metrics, keyword co-occurrence, and author collaboration networks to visualize the conceptual and social structure of the field.Results: The study identified only 10 relevant documents authored by 40 researchers, indicating that Jamasan Pusaka remains a niche but emerging research area. Common keywords included “historic preservation” and “cultural heritage,” suggesting a strong focus on material conservation and symbolic meaning. The tradition’s future is challenged by declining youth engagement, despite its potential in cultural tourism. Author networks showed some collaboration, but interdisciplinary engagement remains limited. Conclusion: Jamasan Pusaka represents a vital intersection of tangible artifacts and intangible cultural values. Despite the existence of impactful core literature, limited scholarly output highlights the need for broader academic involvement. Future research should prioritize qualitative and community-based studies to explore its socio-cultural dimensions. Interdisciplinary collaboration and comprehensive documentation are key to ensuring the tradition’s continuity for future generations.